Learning Multimedia Based on Science Literacy on the Lightning Theme - Rubini, Bibin; Permanasari, Anna; Yuningsih, Winda (Jurnal Penelitian dan Pembelajaran IPA, 2018)
This study aims to develop of multimedia based on science literacy on the lightning themes and apply it on the science learning to improve of students' scientific literacy. The method used in this research is Research and Development with ADDIE (Analysis, Design, Development, Implementation and Evaluation) models. The research design at the multimedia implementation as small scale on the science learning by using one-group pretest-posttest design. Implementation was carried out in class IX with 31 students with cluster random sampling. The result of research showed: (1) multimedia based on science literacy on lightning themes in the form of text, images, animation, and videos that refer to the 2015 PISA framework are content, science competencies and science attitudes domains; (2) the feasibility test by the expert and teacher show all aspects of multimedia have a very good category, it is suitable for use in science learning; and (3) the using of multimedia can increase science literacy skills especially content and scientific attitude domains have medium category. As well as competency domains show is very good categories. This is supported by respon of student that multimedia is very good in the domain aspects of literacy and motivation, whereas in aspect of operating multimedia have good categories.